Governance in Third Sector Organizations: The Indonesian Context - Maria Nindita Radyati (Business and Entrepreneurial Review, 2007)
This research is based on qualitative exploratory research whit the main purpose of looking into the local and unique conception of governance. The questions forwarded here are aimed at investigating Key Informant's (KI) knowledge and understanding about 'governance for Third Sector Organizations (TSO)' and related issues. Ultimately, the findings shows that KIs relate this concept to several similar notions which can be classified into five areas: (1) Internal governance; (2) External governance; (3) System; (4) Managerial functions; (5) Compliance to vision and mission. It is hoped that readers will gain valuable insights from lndonesia's concept of good governance, which weds local conceptions and values to modern theory.